THE INFLUENCE OF VALUE ADDED TAX EXEMPTION TOWARDS PROCESSED SEAWEED EXPORTS OF INDONESIA - Anugrahayu, Nevadea Tiara; Darwanto, Dwidjono Hadi; Jamhari, Jamhari (Berkala Ilmiah AGRIDEVINA, 2017)
Seaweed is one of the prospective cultivated marine commodity that supports fisheryrevitalization program that is enacted by the government. In the downstream, thegovernment has made many efforts to increase the value added gain from this commodity. One of the efforts is by enacting a value added tax exemption policy throughGovernment Regulation about Import and/or Refferal of Certain Strategic Taxable Goodsthat are Free from Added Value Tax. This policy is enacted to encourage the businessworld especially in agriculture, where it is needed to give easier tax facility byestablishing agricultural products that are Taxable Goods. The purpose of this research isto analyze the influence of value added tax exemption policy that is enacted to domesticseaweed processing industry, towards Indonesia’s processed seaweed export. Indonesiawas the world’s biggest seaweed exporter for the last few of years. The government,through its value added tax exemption policy, aimed to encouraged domestic processingindustry to not only exporting seaweed as the raw materials but also to export processedproducts that have added value. The model used in this research was Error CorrectionModel (ECM). This research found that value added tax exemption policy has positiveand significant influences towards processed seaweed export in the long and short-run.This show that the government’s policy in relation to value added tax exemption waseffective in increasing exports.